Urban Flood Control in Sringin Catchment, Semarang City, Central Java Province, Indonesia - Ngo Pheaktra (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
Sringin is the lowland area located in Semarang city which has been vulnerable to rob flooding from the Java Sea along with flood triggered by the intense amount of rainfall. The case study will further discuss the hydrological analysis, transformation of rational method into flow hydrograph with the design rainfall of 25-year return period, and unsteady flow analysis by HEC-RAS 5.0.3 under existing condition and design condition. The result shows that the design rainfall of 25-year return period measures 173 mm in vertical length and data collected from the office of public work, Semarang city can be used to implement the design scenario with normalization of drainage system and the increase of levee with the freeboard up to 0.75 m is proved to be the solution to the flood inundation in that flood-prone area while the flood under existing condition has caused excessive discharge at downstream up to 9 hours.